Method for Automatic Collocation Extraction from Ukrainian Corpora - Kuzmina, M.; Petrasova, S. V. (My University, 2018)
The article deals with the methods for automatic collocation extraction from Ukrainian corpora. The task of collocation extraction is considered in terms of a corpus-oriented approach [1], based on statistical measures. The term «collocation» is defined as a non-random combination of two words that go together regularly.